1977
DOI: 10.1007/bf00380692
|View full text |Cite
|
Sign up to set email alerts
|

The capacity of chlorophyll-a biosynthesis in the mustard seedling cotyledons as modulated by phytochrome and circadian rhythmicity

Abstract: Within the temporal pattern of "primary differentiation" the capacity of chlorophyll - a biosynthesis in the cotyledons ofSinapis alba L. seedlings is controlled by phytochrome (in continuous light) or by releasing the circadian rhythm either with lightdark cycles or by a light→dark transition. The sensor pigment for this process is phytochrome. It is very probable that in continuous light as well as under conditions under which the circadian rhythm plays the major part, the capacity of chlorophyll a biosynthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
5
0
1

Year Published

1979
1979
1995
1995

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 34 publications
3
5
0
1
Order By: Relevance
“…These data indicate that greening and hence chloroplast biogenesis is under circadian control after HS and/or light treatments. Similar findings on Chl accumulation induced via phytochrome have been observed earlier; however, the interpretation of these findings was different (13). Because the same result has not been observed in etiolated plantlets, it would be reasonable to assume that in etiolated plants the circadian clock does not oscillate or, if oscillating, is not under the synchronizing control of a circadian pacemaker but can be synchronized by HS (and/or light).…”
Section: Discussionsupporting
confidence: 67%
“…These data indicate that greening and hence chloroplast biogenesis is under circadian control after HS and/or light treatments. Similar findings on Chl accumulation induced via phytochrome have been observed earlier; however, the interpretation of these findings was different (13). Because the same result has not been observed in etiolated plantlets, it would be reasonable to assume that in etiolated plants the circadian clock does not oscillate or, if oscillating, is not under the synchronizing control of a circadian pacemaker but can be synchronized by HS (and/or light).…”
Section: Discussionsupporting
confidence: 67%
“…2) with an optimum in the blue region of the spectrum are similar to most action spectra for the HIR, at least in this region of the spectrum. For example, similar action spectra have been reported for such diverse responses in higher plants as leaf inclination in wheat (22), ethylene production (3), elongation of hypocotyls in de-etiolated cucumber seedlings (1) and etiolated lettuce seedlings (14,16), and Chl formation in wheat roots (12). Many of these action spectra also show peaks in the far red region of the spectrum.…”
Section: Discussionsupporting
confidence: 57%
“…No diurnal rhythm could be detected in the transcription of genes coding for either PEPc or the cytosolic form of aldolase. Gehring et al (1977) have reported that Chi a biosynthesis in mustard seedlings also shows circadian rhythmicity, so both the synthesis of the pigment and the apoprotein of the Chi a/b complex are regulated by a circadian rhythm. There is also evidence that both the apoprotein gene expression (Nagy et al, 1988) and Chi a gene expression (Gehring, Kasemir & Mohr, 1977) are regulated by phytochrome.…”
Section: Organismsmentioning
confidence: 99%
“…Gehring et al (1977) have reported that Chi a biosynthesis in mustard seedlings also shows circadian rhythmicity, so both the synthesis of the pigment and the apoprotein of the Chi a/b complex are regulated by a circadian rhythm. There is also evidence that both the apoprotein gene expression (Nagy et al, 1988) and Chi a gene expression (Gehring, Kasemir & Mohr, 1977) are regulated by phytochrome. The circadian rhythm in the expression of the cab gene in tomato leaves is regulated by light to dark and dark to light transitions , and by changes in temperature (Piechulla & Reisselmann, 1990).…”
Section: Organismsmentioning
confidence: 99%